Survey and Monitoring of Chinese Citrus Fly (Bactrocera minax Enderlein) in Sweet Orange Orchards of Sindhuli, Nepal - Gautam, Elina; Srivastava, Arvind; Singh, Lalan Kumar; Karki, Shanta; Adhikari, Debraj; Acharya, Umesh; Thapa, Resham Bahadur (Nepalese Horticulture, 2020)
Chinese citrus fly, Bactrocera minax (Enderlein), is one of the most important pests of citrus. The pest is more problematic in the eastern part of the country, Nepal. Because of the difficulties associated with the control of this pest by chemical insecticides, farmers had experienced great losses in Sweet Orange. Therefore, a participatory field survey was conducted under farmer field conditions to assess losses and measure the efficacy of different local and recommended management options to address the problem of this pest. Study consisted of two major parts: monitoring of pest population and farmer’s survey. For monitoring three orchards were selected located at different altitude i.e. 1200 masl, 1300 masl and 1400 masl. Great Fruit fly Bait (25% protein hydrolysate and 0.1% abamectin) in McPhail traps were used for monitoring. Monitoring was done in every 7 days interval and lures were changed in every 15 days for the effectiveness. Only 18.3% farmers were using protein bait for the management of fruit fly. B. minax had peak population intensity at May and was found decreasing after June so the management practices should be adopted before June to prevent the loss by fruit fly. However, for best effective control attention for monitoring and management procedures has to take place throughout the life cycle of the insect.